2018
DOI: 10.3847/2041-8213/aaa839
|View full text |Cite
|
Sign up to set email alerts
|

Gaia DR1 Evidence of Disrupting the Perseus Arm

Abstract: We have discovered a clear sign of the disruption phase of the Perseus arm in the Milky Way using Cepheid variables, taking advantage of the accurately measured distances of Cepheids and the proper motions from Gaia Data Release 1. Both the Galactocentric radial and rotation velocities of 77 Cepheids within 1.5 kpc of the Perseus arm are correlated with their distances from the locus of the Perseus arm, as the trailing side is rotating faster and moving inward compared to the leading side. We also found a nega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 46 publications
4
32
0
Order By: Relevance
“…The location of the Perseus arm coincides with high density clouds in between our predicted two dashed lines. This is in agreement with the recent finding of Baba et al (2018) which uses data from Gaia DR1 concluding that the Perseus arm is being disrupted.…”
Section: Galactic Dust Mapsupporting
confidence: 93%
“…The location of the Perseus arm coincides with high density clouds in between our predicted two dashed lines. This is in agreement with the recent finding of Baba et al (2018) which uses data from Gaia DR1 concluding that the Perseus arm is being disrupted.…”
Section: Galactic Dust Mapsupporting
confidence: 93%
“…Thus, they are the result of perturbations induced by current spiral structures according to Siebert et al (2012). However, it is noted that they assume a steady spiral structure in their simulation, while the origin of the spiral structures is far from clear (Baba et al 2018;Tchernyshyov et al 2018;Sellwood et al 2018). Therefore, our results may not clearly exclude the perturbation of spiral arms originated from other mechanism but only rule out a steady density wave spiral structure.…”
Section: Discussionmentioning
confidence: 97%
“…Hunt et al (2018) show that ridges in the same stellar velocity distribution resemble predictions from the dynamic model. An analysis of Cepheid velocities based on Gaia DR1 data by Baba et al (2018) found that the Perseus arm is likely to be a dynamic arm in the dissipation phase.…”
Section: Discussionmentioning
confidence: 99%